Gender on ice : American ideologies of polar expeditions - Bloom, Lisa E., 1958- (American culture (Minneapolis, Minn.), 1993)
Bloom focuses on the conquest of the North Pole as she reveals how popular print and visual media defined and shaped American national ideologies from the early twentieth century to the present.